النزعة الإنسانية في شعر محمود درويش - مقاربة تفكيكية لنماذج مختارة - بلعالم عبلة (My University, 2025)
Summary: This study explores "The Humanistic Tendency in the Poetry of Mahmoud Darwish: A Deconstructive Approach to Selected Models", a topic that highlights the human dimension in Mahmoud Darwish's poetic experience, whose name is deeply linked to the Palestinian cause. The importance of this topic lies in: - Highlighting the human aspect of Mahmoud Darwish’s experience. - Offering a new reading that allows for deep exploration into his poetic worlds, which express human anxiety. - The study is divided into two parts: a theoretical framework and a practical application. In the theoretical part, we addressed: - The conceptual framework of the study: Humanistic tendency – Humanization – Humanism – Humanist doctrine. - The main features, issues, and tools of the humanistic tendency. - The study of the humanization tendency in both Arab and Western thought. - The manifestations of humanism in Arabic poetry. In the practical part, we discussed: - The dimensions of humanism in Mahmoud Darwish’s poetry. - A deconstructive study of excerpts from “The Stranger’s Bed” (Sareer Al-Ghariba) by Mahmoud Darwish. - We also examined the language, intertextuality, and myth in this collection. Through this study, we arrived at the following conclusions: - The humanistic tendency focuses on the human being, emphasizing their freedom and dignity. - Mahmoud Darwish called for the freedom of peoples, expressed his attachment to his homeland, and rejected oppression and tyranny. - The estrangement and exile experienced by Mahmoud Darwish led him to focus on human aspirations, hopes, and expressions of suffering. - Mahmoud Darwish's poetic experience reveals a sophisticated condensation of the idea of man as an active, reflective, and resistant self seeking to assert its existence in a world. - The collection "The Bed of Arabic" represents a mature phase in Mahmoud Darwish's poetic experience, where personal and emotional dimensions intertwine. Alienation, women, and exile, which Darwish represented as symbols of the brokenness of the Palestinian self and the hope of transcending reality, are evident ------------------ الملخص: تتناول هذه الدراسة "النزعة الإنسانية في شعر محمود درويش مقاربة تفكيكية لنماذج مختارة " و هو موضوع يسلط الضوء على البعد الإنساني في تجربة محمود درويش الذي ارتبط اسمه بالقضية الفلسطينية. حيث تكمن أهمية الموضوع في: - ابراز البعد الإنساني في تجربة محمود درويش. - تقديم قراءة جديدة تتيح المجال للغوص في عوالمه الشعرية العميقة التي تعبر عن قلق الإنسان. - تطرقنا في هذه الدراسة إلى جانبين: جانب نظري وجانب تطبيقي. تطرقنا في الجانب النظري إلى: - الإطار المفهومي للدراسة: النزعة الإنسانية - نزعة الأنسنة -الإنسانية - المذهب الإنساني - ذكر أهم خصائص النزعة الإنسانية وإشكالياتها وأدواتها - دراسة نزعة الأنسنة في الفكر العربي والغربي - ذكر تجليات النزعة الإنسانية في الشعر العربي أما بالنسبة للجزء التطبيقي تطرقنا إلى: - أبعاد النزعة الإنسانية في شعر محمود درويش - دراسة تفكيكية لمقتطفات من ديوان سرير الغريبة لمحمود درويش وأخيرا درسنا اللغة والتناص والأسطورة لهذا الديوان ومن خلال دراستنا لهذا الموضوع تحصلنا على النتائج التالية: - النزعة الإنسانية تركز اهتمامها على الإنسان وتؤكد على حريته وكرامته. - دعوة محمود درويش إلى حرية الشعوب، والتعبير عن تعلقه بوطنه، ونبذ الظلم والاستبداد. - الغربة والبعد عن الوطن التي عايشها محمود درويش جعلته يركز على تطلعات الإنسان وآماله والتعبير عن معاناته. - تظهر تجربة محمود درويش الشعرية تكثيفا راقيا لفكرة الإنسان كذات فاعلة، متأملة، ومقاومة تسعى إلى إثبات وجودها في العالم. - شکل دیوان سرير الغريبة مرحلة ناضجة في التجربة الشعرية لمحمود درويش، حيث تتداخل فيه الأبعاد الذاتية والعاطفية. وقد ظهر ذلك من خلال الغربة والمرأة والمنفى التي تشكلت عند درويش رموزا لانكسارات الذات الفلسطينية والأمل في تجاوز الواقع. --------------------- Résumé : Cette étude intitulée "La tendance humaniste dans la poésie de Mahmoud Darwich: une approche déconstructiviste de modèles choisis" met en lumière la dimension humaine dans l'œuvre de Mahmoud Darwich, dont le nom est étroitement lié à la cause palestinienne. L'importance de ce sujet réside dans : - La mise en valeur de l'aspect humain dans l'expérience poétique de Mahmoud Darwich. - La présentation d'une nouvelle lecture permettant d'explorer les profondeurs de son univers poétique, qui exprime l'angoisse de l'être humain. - L'étude comporte deux volets : un volet théorique et un volet pratique. Dans la partie théorique, nous avons abordé : - Le cadre conceptuel de l'étude : la tendance humaniste, l'humanisation, l'humanisme et la philosophie humaniste. - Les principales caractéristiques, problématiques et outils de la tendance humaniste. - L'étude de l'humanisation dans la pensée arabe et occidentale. - Les manifestations de la tendance humaniste dans la poésie arabe. Quant à la partie pratique, nous avons exploré : - Les dimensions de la tendance humaniste dans la poésie de Mahmoud Darwich. - Une analyse déconstructiviste d'extraits du recueil "Le Lit de l'Étrangère" de Mahmoud Darwich. - L'étude du langage, de l'intertextualité et du mythe dans ce recueil. À travers cette étude, nous avons abouti aux résultats suivants : - La tendance humaniste met l'accent sur l'être humain, affirmant sa liberté et sa dignité. - L'appel de Mahmoud Darwich à la liberté des peuples, son attachement à sa patrie et son rejet de l'oppression et de la tyrannie. - L'exil et l'éloignement de sa terre natale ont poussé Mahmoud Darwich à se concentrer sur les aspirations et les espoirs de l'homme, en exprimant ses souf. - L’expérience poétique de Mahmoud Darwish révèle une condensation sophistiquée de l’idée de l’homme comme un soi actif, réfléchi et résistant s’efforçant de prouver son existence dans le monde. - Le Bed Diwan arabe représente une étape de maturité dans l’expérience poétique de Mahmoud Darwish, dans laquelle les dimensions personnelles et émotionnelles s’entremêlent. Il est devenu clair pour vous que l’exil, les femmes et l’aliénation, que Darwish représentait, sont des symboles des défaites de l’identité palestinienne et de l’espoir de transcender la réalité
Keywords: Mahmoud Darwish; humanism; resistance; freedom.; محمود درويش، النزعة الانسانية، المقاومة، نزعة الانسنة، الحرية.; Mahmoud Darwich; humanisme; résistance; liberté